Uso de aditivos alimentares e coprodutos do etanol de milho na dieta de bovinos de corte - Ormond, Victoria Curvo (2023)
Two experiments were conducted to evaluate the effects of the use of feed additives and corn ethanol by-products in the diet of beef cattle. In Exp. 1 the effects of different additives were evaluated on the kinetic parameters of gas production and DM and NDF digestibility. In Exp. 2, the effects of the inclusion of Dry Distillers Bran plus Solubles (DDBS) and Dry Distillers with Solubles (DDGS) as sources of protein and energy in non-forage diets on the nutrient intake and digestibility, performance, and blood metabolic parameters of growing beef cattle were evaluated. In Exp. 1 the following additives were evaluated: control (CON) - (without the inclusion of additives); Monensin (MON) - (20 mg/kg DM); Flavomycin (FLAVO) - (4 mg/kg DM); Live yeasts (VL) - Saccharomyces cerevisiae - (0.5 g/kg DM, UFC/mg?); Yeast culture (LC1) – (1.3 g/kg DM); Culture of yeast (LC2) - (1.3 g/kg DM) and Functional Oils (OF) - (3.5 g/kg DM). The substrates used were Urochloa brizantha cv. Xaraés, DDBS – Dry Distillers Bran plus Solubles (dry fiber from distillers grains with solubles), and the combination of the both (50:50). In Exp. 2, the treatments consisted of three non-forage diets: Control - diet formulated with conventional ingredients (soybean hulls, corn, soybean meal, cotton cake, urea and mineral mix); DDGS – diet with inclusion of 30% DDGS; and DDBS – diet with inclusion of 30% of DDBS. In Exp. 1 the ruminal fluid was obtained from two rumen fitted, castrated, 14 months old F1 Nelore x Angus steers, which were kept under grazing and receiving mineral salt without additives. Three consecutive incubations were performed. Gas production (GP) was measured at 3, 6, 9, 12, 18, 24, 36 and 48 hours of incubation with a semi-automatic pressure transducer. A total of 67 vials per incubation (7 additives x 3 substrates x 3 replicates) and four more vials as blanks were used. In Exp. 2, 24 Nellore uncastrated males (BW = 276 kg ± 36.1 kg) were randomly distributed in 12 pens (2 animals/pen) considering a randomized block design. In Exp. 1 there was no interaction of additives x substrates for any of the variables analyzed (P>0.05). There was a higher asymptotic gas production (P<0.05) for the forage substrate + DDBS, intermediate for DDBS and lower for forage. For the additives, there was higher gas production when FLAVO was used (P<0.05), with no differences between the other additives. The inclusion of MON and FLAVO reduced (P<0.05) the digestion rate. The lag time was higher when only forage was used as substrate (P<0.05), with no differences between the additives. MON and FLAVO reduced the DM and NDF digestibility as well as N-NH3 concentration (P<0.05). The lower pH was observed when MON (P<0.05) was used, but for substrates there was no significant difference (P>0.05). DDBS stimulated the synthesis of microbial biomass compared to control (P<0.05) although there was no significant difference for additives. In Exp. 2, the inclusion of DDGS and DDBS increased dry matter intake in relation to the control (P<0.05). The intake of CP, EE and NDF were higher for DDGS, intermediate for DDBS and lower for control (P<0.05). The inclusion of corn ethanol byproducts improved the digestibility of nutrients when compared to the control (P<0.05). The ADG was higher (P<0.05) for the animals fed with DDGS when compared to the control and DDBS, which did not differ from each other. The rate of weight gain was also higher, and the feed conversion (kg/kg) was better for the animals fed DDGS when compared to the control and DDBS, which did not differ from each other. The inclusion of DDBS and DDGS did not influence (P>0.05) the blood parameters. It is concluded (Exp. 1) that regardless of the substrate, the inclusion of FLAVO enables greater gas production in vitro. The additives MON and FLAVO caused a deleterious effect on the digestion of DM and NDF. In Exp. 2 the positive effect of DDGS on animal performance may be associated with higher nutrient intake.